2005
DOI: 10.1080/02841850500225740
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided core needle biopsy of non-palpable breast lesions: a prospective analysis in 204 cases

Abstract: US-guided core needle biopsy is a sensitive percutaneous biopsy method for diagnosing non-palpable breast lesions. To achieve a high diagnostic yield, a minimum number of three cores per lesion is advisable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 24 publications
1
20
0
3
Order By: Relevance
“…It has been reported that the false negative rate of CNB is 1.1% to 3.3%, [6][7][8][9][10][11][12][13][14] whereas the corresponding rate of VAB is 0.6% to 3.5%. [15][16][17][18] Among lesions with ultrasonographyehistologic discordance, 21.4% are upgraded in the pathological diagnosis after VAB, according to Li et al 19 Furthermore, it has also been reported that VAB might be valuable for definitive diagnosis when pathological results with CNB are discordant with imaging findings.…”
Section: Discussionmentioning
confidence: 95%
“…It has been reported that the false negative rate of CNB is 1.1% to 3.3%, [6][7][8][9][10][11][12][13][14] whereas the corresponding rate of VAB is 0.6% to 3.5%. [15][16][17][18] Among lesions with ultrasonographyehistologic discordance, 21.4% are upgraded in the pathological diagnosis after VAB, according to Li et al 19 Furthermore, it has also been reported that VAB might be valuable for definitive diagnosis when pathological results with CNB are discordant with imaging findings.…”
Section: Discussionmentioning
confidence: 95%
“…For example, in a recent study by VEGA-BOLIVAR et al (22), a minimum of three cores per lesion obtained under US guidance of nonpalpable breast lesions was recommended. Our current results suggest that core needle biopsy with a 14/16-gauge needle is a reliable method in differentiating true fibroadenomas from phyllodes tumors.…”
Section: Discussionmentioning
confidence: 98%
“…The differences in diagnosis rates may be attributed to differences in CNB apparatuses or operational skills, but these differences may also stem from the objectives and methods of individual studies, including sample size, cohort characteristics, the presence or absence of an FA control group, and the presence or absence of a review of the CNB results. Bolívar et al (26) proposed obtaining a minimum of three specimens via ultrasound-guided CNB for cases of breast tumors that were difficult to examine via palpation. Bode et al (11) reported that using 14 G or 16 G biopsy needles could deliver a relatively improved outcome in differentiating a PTB specimen from that of FA.…”
Section: Discussionmentioning
confidence: 99%